« Une vieille matière d’une manière nouvelle » ou comment romancer la Vie de sainte : Roselis ou l’histoire de sainte Suzanne de Jean-Pierre Camus (1623) - Nancy Oddo (Les Dossiers du GRIHL)
In his notice to the reader in Roselis oul’Histoire de sainte Susanne (1623), Jean-Pierre Camus, a French bishop who is also a novelist, declares that he is renewing the writing of Saint’s Life using a new poetics specified in a large peritext. Besides changing the name of the saint, he writes digressions which prevail over the narration. He uses the energeiarhetoric in his dialogues, descriptions, analogies and author intrusions: the paradoxical effect is to rule out the emotions of the reader. Within the narrative, its aesthetics (varietas) and its pragmatics actualize and concretize his own advices. The polemic aim (against Protestants) and the politic function (defending Louis XIII during his return trip after his victory in Languedoc) are the most important elements of his work. Roselis christianises both the royal encomiastic and Susannah herself (at this time, Susannah at her bath is most often naked). Camus takes down the erotic overtones, to remind the Christian meaning of baptism.